THU0362 PREDICTORS OF MORTALITY IN SYSTEMIC SCLEROSIS. (2nd June 2020) - DE Almeida Chaves, S.; Porel, T.; Adoue, D.; Astudillo, L.; Ribes, D.; Prévot, G.; Gaches, F.; Alric, L.; Sailler, L.; Pugnet, G.
Abstract : Background: Systemic sclerosis (SSc) is known as the most severe connective tissue disorder, and to be associated with a high mortality risk. Moreover, there is a great variability of mortality rate in the literature. Objectives: To determine the mortality rate and its predictors in systemic sclerosis in a long-term follow- up of a bi-centric cohort of SSc patients Methods: We have carried out a retrospective observational study by systematically analysing the medical records of patients diagnosed with SSc in Toulouse University Hospital and Ducuing Hospital. We included patients over 18 years old, whose diagnosis was made after 01/01/2000 and who met the classification criteria for the American College of Rheumatology (ACR) /EULAR 2013, and with at least one follow-up visit after the inclusion visit. Patients were followed until 30/05/2018. We quantified mortality as Standardized Mortality Ratio (SMR) and percentage mortality at 1, 3, 5, 10 and 15 years of disease. For comparison, we used the mortality rate for the population in the French Region of Occitanie in 2016, using data from the French National Statistical Agency. We determined a single primary cause of death (SSc or non-SSc related) and evaluated predictors of mortality using multivariable Cox regression. Results: We included 375 patients (292 females), 63 (15.2%) patients with diffuse cutaneous SSc, 279 (76.7%) with limited cutaneous SSc and 33 (8.1%) with sine scleroderma SSc. During the study period 6 patients were lost to follow-up and 69 died (18.4%). The SMR ratio was 1.85 (95% CI 1.45-2.34). The overall survival rates were 97.5% at 1 year, 93.4% at 3 years, 87.1% at 5 years, 77.9% at 10 years and 61.3% at 15 years. Among the 69 deaths recorded 46.4% were SSc related deaths, 53.6% were non-related. Among the SSc related deaths, three main causes were identified: interstitial lung disease (ILD) (34.4%), pulmonary hypertension (31.2%) and digestive tract involvement (18.8%). Among the causes of SSc non-related deaths, cardiovascular disorders (37.8%) and various infections (35.1%) largely distanced those from cancer (13.5%). Four significant independent predictive factors were identified using multivariable Cox regression: carbon monoxide diffusing capacity ( DLCO ) < 70% (HR=3.01; p=0.0053), C-reactive protein (CRP) >5 mg/l (HR=2.13; p=0.0174), cardiac involvement (HR=2.86; p=0.0012) and the fact of being male (HR=3.25; p=0.0004) (Table 1 ). The same four factors were identified as predictive of mortality at 5 and 10 years in multivariable Cox regression (Table 2 ). Conclusion: Our results confirm that SSc is a devastating condition as reflected by a pooled SMR of 1.85. The two principal causes of SSc-related death remain PH and ILD. However, SSc non-related death are represented mainly by cardiovascular diseases. This work identified sex (male), DLCO <70%, cardiac involvement and CRP> 5mg/l as independent predictors of mortality. With the emergence of new therapies, these important observations should help refine the monitoring and management to prolong these patients' survival. Disclosure of Interests: None declared